THE INTEGRATION OF WORDWALL GAMIFICATION WITHIN THE TEAM GAMES TOURNAMENT MODEL: ITS IMPACT ON ELEMENTARY STUDENTS` MATHEMATICS LEARNING OUTCOMES - Lutfiyah Sari, Yessy; Zahrani Susilo, Claudya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of integrating Wordwall-based gamification within the Team Games Tournament (TGT) learning model on elementary students’ mathematics learning outcomes. The research was motivated by the low mathematics achievement of students, which is often associated with teacher-centered instructional practices and limited student engagement. A quantitative approach with a pre-experimental design, specifically the one-group pretest–posttest design, was employed in this study. The participants consisted of 30 fourth-grade students at SDN Grogol 2, Jombang Regency, selected using a saturated sampling technique.Data were collected through learning achievement tests administered before (pretest) and after (posttest) the implementation of the instructional treatment. The data were analyzed using descriptive statistics and inferential analysis, including the Shapiro–Wilk normality test and paired sample t-test. The results revealed a significant improvement in students’ learning outcomes, as indicated by the increase in the mean score from 64.7 in the pretest to 81.46 in the posttest. In addition, the percentage of students achieving mastery learning increased from 13.33% to 90%. The hypothesis testing showed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between pretest and posttest results. These findings demonstrate that the integration of Wordwall gamification within the TGT model effectively enhances students’ mathematics learning outcomes. This improvement is supported by increased student engagement, active participation, collaborative learning, and higher motivation fostered through game-based and interactive learning environments. In conclusion, the integration of Wordwall gamification within the Team Games Tournament model can be considered an effective and innovative instructional strategy to improve mathematics learning outcomes in elementary education